Longitudinal radiographic behavior of accessory navicular in pediatric patients. (December 2016) - Knapik, Derrick M.; Guraya, Sahejmeet S.; Conry, Keegan T.; Cooperman, Daniel R.; Liu, Raymond W.
Background: An accessory navicular is generally asymptomatic and discovered incidentally on radiographs. The natural history of an accessory navicular in the pediatric population is largely undescribed. Methods: The medical charts of 261 pediatric subjects undergoing 2620 annual unilateral radiographs of the foot and ankle (age range 0.25–7 years at enrollment) were reviewed. Radiographs were examined to determine the incidence of accessory navicular, with focus on the age at appearance and, if present, the age at fusion. Skeletal maturity was graded based on ossification pattern of the calcaneal apophysis. Results: Accessory navicular was identified in 19 subjects ( n = 12 males, n = 7 females, p = 0.43), appearing significantly earlier in the female subjects than in the male ones ( p = 0.03). Fusion was documented in 42% ( n = 8) of subjects, occurring at a mean (±standard deviation) age of 12.5 ± 1.0 years in females and 14.1 ± 2.7 years in males. Skeletal maturity grading demonstrated comparable stages of maturity at the time of fusion between male and female subjects ( p = 0.5). Based on an analysis of 160 subjects with serial images extending at least one standard deviation past the mean age of appearance, the overall incidence was 12%. Conclusion: Our review of pediatric subjects showed that accessory navicular appeared earlier in females than in males. Fusion occurred in 42% of patients at comparable levels of skeletal maturity between the male and female subjects. No significant differences in overall incidence, skeletal maturity, fusion rate, or age of fusion were noted between the male and female subjects.